2015
DOI: 10.1007/s11434-015-0911-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of multi-GNSS between-receiver differential code biases using zero and short baselines

Abstract: Care should be taken to minimize adverse impact of receiver differential code biases (DCBs) on global navigation satellite system (GNSS)-derived ionospheric parameters. It is therefore of importance to ascertain the intrinsic characteristics of receiver DCBs, preferably in the context of new-generation GNSS. In this contribution, we present a method that enables time-wise retrieval of between-receiver DCBs (BR-DCBs) from dualfrequency, code-only measurements collected by a pair of co-located receivers. This me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 35 publications
0
44
0
Order By: Relevance
“…Interestingly, it is found that, both time series are slightly different in the magnitude, but remarkably similar in the trend. The difference can be attributed to the fact that, the receiver bias value usually depends, in addition to other factors such as hardware and antenna, on the GNSS constellation (Zhang and Teunissen 2015). On the other hand, the similarity lies particularly in the fact that the same (or, at least, close to the same) oscillating behavior is simultaneously present in both time series, and that oscillation occurs every day between 01:00 GPST (09:00 LT) and 13:30 GPST (21:30 LT), corresponding exactly to the time interval when the air-conditioning system is on.…”
Section: Characterization Of Br-dpb Estimatesmentioning
confidence: 99%
“…Interestingly, it is found that, both time series are slightly different in the magnitude, but remarkably similar in the trend. The difference can be attributed to the fact that, the receiver bias value usually depends, in addition to other factors such as hardware and antenna, on the GNSS constellation (Zhang and Teunissen 2015). On the other hand, the similarity lies particularly in the fact that the same (or, at least, close to the same) oscillating behavior is simultaneously present in both time series, and that oscillation occurs every day between 01:00 GPST (09:00 LT) and 13:30 GPST (21:30 LT), corresponding exactly to the time interval when the air-conditioning system is on.…”
Section: Characterization Of Br-dpb Estimatesmentioning
confidence: 99%
“…First, original dual-frequency GPS phase and pseudo-range data from the 21 selected sites were preprocessed by removing gross errors and then detecting and repairing cycle slips using Melbourne-Wuebbena linear combinations, geometry-free linear combinations, and ionosphere-free linear combinations (for more details, refer to [40][41][42][43][44]). Then, we calculated the ROT along the signal paths (epoch by epoch), which allowed us to obtain the corresponding TEC fluctuation index ROTI.…”
Section: Methods and Data Processingmentioning
confidence: 99%
“…One strategy fixes the DCBs of a receiver or satellite, with the DCB parameters of the other receivers and satellites to be solved afterwards. Another strategy adopts the DCBs gravity datum of one satellite as the constraint , and it is assumed that the sum of all the satellite DCBs of that satellite is zero; thus, the equation of the gravity datum is dcbitalici,italicj1++dcbitalici,italicjn=0 …”
Section: Mathematical Modelmentioning
confidence: 99%